2022
DOI: 10.3389/fgene.2022.977902
|View full text |Cite
|
Sign up to set email alerts
|

An oxidative stress-related prognostic signature for indicating the immune status of oral squamous cell carcinoma and guiding clinical treatment

Abstract: Oral squamous cell carcinoma (OSCC) is the eighth most common cancer worldwide and presents high mortality. Oxidative stress, caused by reactive oxygen species accumulation, plays a crucial role in tumorigenesis, cancer progression, and drug resistance. Nevertheless, the specific prognostic and clinical values of oxidative stress-related genes (OSGs) in OSCC remain unclear. Here, we developed an oxidative stress-related prognostic signature according to mRNA expression data from The Cancer Genome Atlas (TCGA) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 68 publications
(75 reference statements)
0
2
0
Order By: Relevance
“…12,14,15,24 Moreover, quantifying ROS expression can contribute to our understanding of the mechanisms underlying oral cancer and aid in the development of preventative therapies and treatments. 14,25,41,42 Elevated production and accumulation of ROS within cells can result in oxidative damage, including alterations in ΔΨm. 4,43 Our results showed a significant decrease in the intracellular expression of ΔΨm in oral exfoliated cells exposed to H 2 O 2 compared to non-exposed cells, which is consistent with previous studies.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…12,14,15,24 Moreover, quantifying ROS expression can contribute to our understanding of the mechanisms underlying oral cancer and aid in the development of preventative therapies and treatments. 14,25,41,42 Elevated production and accumulation of ROS within cells can result in oxidative damage, including alterations in ΔΨm. 4,43 Our results showed a significant decrease in the intracellular expression of ΔΨm in oral exfoliated cells exposed to H 2 O 2 compared to non-exposed cells, which is consistent with previous studies.…”
Section: Discussionmentioning
confidence: 99%
“…Measuring ROS expression within oral cells can be a valuable tool for assessing cellular health and identifying potential oral health risks 12,14,15,24 . Moreover, quantifying ROS expression can contribute to our understanding of the mechanisms underlying oral cancer and aid in the development of preventative therapies and treatments 14,25,41,42 …”
Section: Discussionmentioning
confidence: 99%
“…In addition, accumulating evidences indicated that oxidative stress not only associated with tumor progression but also affected both the tumor microenvironment and the immunotherapy responses (23-25). In recent years, many studies focused on constructing prognostic signature for predicting prognosis and sensitivity to treatment of cancers (18)(19)(20)(21). Hence, constructing a risk prognostic signature using ORGs for predicting clinical outcome of ccRCC may be promising.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, high levels of ROS also could affect the tumor development through influencing chemotherapeutic resistance and inducing cell apoptosis (15-17). Recent studies have shown that ORGs signature could be used as a biomarker for predicting clinical outcome and treatment responses in many cancers (18)(19)(20)(21). In urologic cancer, ORGs signature was developed for predicting clinical outcome and immune status in patients with bladder cancer (22).…”
Section: Introductionmentioning
confidence: 99%
“…Based on mRNA expression data from the TCGA database, Lu et al created an oxidative stress-related prognostic signature and assessed its relationships with OSCC prognosis, clinical characteristics, immunological status, immunotherapy, and medication sensitivity through a number of bioinformatics analysis [201]. The signature was demonstrated to be an independent prognostic factor with high accuracy and was proven to be a good indicator for predicting the prognosis and immunological state of patients with OSCC on the basis of both the TCGA-OSCC and GSE41613 cohorts.…”
Section: Oral Squamous Cell Carcinomamentioning
confidence: 99%